Potential for the use of mHealth in the management of cardiovascular disease in Kerala: a qualitative study. Issue 11 (17th November 2015) - Smith, Rebecca; Menon, Jaideep; Rajeev, Jaya G; Feinberg, Leo; Kumar, Raman Krishan; Banerjee, Amitava
Abstract : Objectives: To assess the potential for using mHealth in cardiovascular disease (CVD) management in Kerala by exploring: (1) experiences and challenges of current CVD management; (2) current mobile phone use; (3) expectations of and barriers to mobile phone use in CVD management. Design: Qualitative, semistructured, individual interviews. Setting: 5 primary health centres in Ernakulam district, Kerala, India. Participants: 15 participants in total from 3 stakeholder groups: 5 patients with CVD and/or its risk factors, 5 physicians treating CVD and 5 Accredited Social Health Activists (ASHAs). Patients were sampled for maximum variation on the basis of age, sex, CVD diagnoses and risk factors. All participants had access to a mobile phone. Results: The main themes identified relating to the current challenges of CVD were poor patient disease knowledge, difficulties in implementing primary prevention and poor patient lifestyles. Participants noted phone calls as the main function of current mobile phone use. The expectations of mHealth use are to: improve accessibility to healthcare knowledge; provide reminders of appointments, medication and lifestyle changes; save time, money and travel; and improve ASHA job efficacy. All perceived barriers to mHealth were noted within physician interviews. These included fears of mobile phones negatively affecting physicians' roles, the usability of mobile phones, radiation and the need for physical consultations. Conclusions: There are three main potential uses of mHealth in this population: (1) as an educational tool, to improve health education and lifestyle behaviours; (2) to optimise the use of limited resources, by overcoming geographical barriers and financial constraints; (3) to improve use of healthcare, by providing appointment and treatment reminders in order to improve disease prevention and management. Successful mHealth design, which takes barriers into account, may complement current practice and optimise use of limited resources.